1996
DOI: 10.1083/jcb.133.4.733
|View full text |Cite
|
Sign up to set email alerts
|

The ion channel activity of the influenza virus M2 protein affects transport through the Golgi apparatus.

Abstract: High level expression of the M2 ion channel protein of influenza virus inhibits the rate of intracellular transport of the influenza virus hemagglutinin (HA) and that of other integral membrane glycoproteins. HA coexpressed with M2 is properly folded, is not associated with GRP78- BiP, and trimerizes with the same kinetics as when HA is expressed alone. Analysis of the rate of transport of HA from the ER to the cis and medial golgi compartments and the TGN indicated that transport through the Golgi apparatus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
174
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 91 publications
(151 reference statements)
9
174
0
2
Order By: Relevance
“…Upon monensin treatment, swollen vesicles emerged near the nucleus (Panels D and G), and YFP-Golgi marker was located in the membrane of these vesicles (Panels E, F, H and I), which is consistent with previous studies (Dinter and Berger, 1998;Tartakoff, 1983). This suggests that most of these swollen vesicles were derived from the Golgi apparatus, and that monensin is effective in HeLa cells, in accord with the findings of Lamb and colleagues that monensin treatment inhibits post-Golgi transport of viral HA protein in HeLa cells (Sakaguchi et al, 1996). After 12 h of monensin treatment, the cytosol of HeLa cells was filled with numerous swollen vesicles (Panel J) in which YFP-Golgi was localized (Panels K and L).…”
Section: Monensin Acts As a Golgi Disruptor In Hela Cellssupporting
confidence: 81%
“…Upon monensin treatment, swollen vesicles emerged near the nucleus (Panels D and G), and YFP-Golgi marker was located in the membrane of these vesicles (Panels E, F, H and I), which is consistent with previous studies (Dinter and Berger, 1998;Tartakoff, 1983). This suggests that most of these swollen vesicles were derived from the Golgi apparatus, and that monensin is effective in HeLa cells, in accord with the findings of Lamb and colleagues that monensin treatment inhibits post-Golgi transport of viral HA protein in HeLa cells (Sakaguchi et al, 1996). After 12 h of monensin treatment, the cytosol of HeLa cells was filled with numerous swollen vesicles (Panel J) in which YFP-Golgi was localized (Panels K and L).…”
Section: Monensin Acts As a Golgi Disruptor In Hela Cellssupporting
confidence: 81%
“…2B expression also alters cellular trafficking, evidenced by effects on the passage of vesicular stomatitis virus G glycoprotein to the cell surface (Doedens & Kirkegaard, 1995). Expression of both IAV M2 (Ciampor et al, 1992a(Ciampor et al, , b, 1995Sakaguchi et al, 1996;Takeuchi & Lamb, 1994;Takeuchi et al, 1994) and HCV p7 (Griffin et al, 2004;Wozniak et al, 2010) has been shown to induce a monensin-like de-acidification of the trans-Golgi/endosomal system, which serves to protect acid-labile proteins/particles during egress. This effect is highly likely to dysregulate cellular trafficking and the resultant surface expression of various proteins.…”
Section: Effects Of Viroporin Channel Activity On Cellular Homeostasismentioning
confidence: 99%
“…6,19 M2 proton channel activity is known to be cytotoxic in heterologous expression systems, such as E. coli, 20,21 with especially severe effects seen in insect cells and S. cerevisiae, with no overt toxicity observed in vertebrate cells. 21,22 …”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%